Hepatic and serum branched-chain fatty acid profile in patients with nonalcoholic fatty liver disease: A case–control study - Martínez-Montoro, José Ignacio; Nuñez-Sanchez, María Ángeles; Martinez-Sanchez, María Antonia; Balaguer-Román, Andrés; Fernández-Ruiz, Virginia E.; Ferrer-Gómez, Mercedes; Sledzinski, Tomasz; Frutos, María Dolores; Fernández-García, José Carlos; Mika, Adriana; Ramos-Molina, Bruno (Wiley, 2023)
Objective Alterations in the hepatic lipidome are a crucial factor involved in the pathophysiology of nonalcoholic fatty liver disease (NAFLD). The aim of this study was to evaluate the serum and hepatic profile of branched-chain fatty acids (BCFAs) in patients with different stages of NAFLD. Methods This was a case–control study performed in 27 patients without NAFLD, 49 patients with nonalcoholic fatty liver, and 17 patients with nonalcoholic steatohepatitis, defined by liver biopsies. Serum and hepatic levels of BCFAs were analyzed by gas chromatography–mass spectrometry. The hepatic expression of genes involved in the endogenous synthesis of BCFAs was analyzed by real-time quantitative polymerase chain reaction (RT-qPCR). Results A significant increase in hepatic BCFAs was found in subjects with NAFLD compared with those without NAFLD; no differences were observed in serum BCFAs between study groups. Trimethyl BCFAs, iso-BCFAs, and anteiso-BCFAs were increased in subjects with NAFLD (either nonalcoholic fatty liver or nonalcoholic steatohepatitis) compared with those without NAFLD. Correlation analysis showed a relationship between hepatic BCFAs and the histopathological diagnosis of NAFLD, as well as other histological and biochemical parameters related to this disease. Gene expression analysis in liver showed that the mRNA levels of BCAT1, BCAT2, and BCKDHA were upregulated in patients with NAFLD. Conclusions These results suggest that the increased production of liver BCFAs might be related to NAFLD development and progression.
Keywords: Hígado -- Enfermedades; Fisiología patológica; Hígado graso